Effectiveness of Acceptance and Commitment Therapy on Alexithymia in Women Experiencing Infidelity - Karimi, Zohreh; Mirhashemi, Malek; Kord, Bahman (Psychology of Woman Journal, 2023)
Objective: Marital infidelity, which signifies a breach of commitment between husband and wife, leads to varying degrees of emotional and physical connection with someone outside the marital relationship. The aim of this study was to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) on alexithymia in women experiencing infidelity. Methods and Materials: The research method was a quasi-experimental design utilizing pre-tests, post-tests, and control and experimental groups. The study population consisted of all women affected by infidelity who sought counseling in Qom (Fardaye Roshan and Shamim Counseling Centers). The sampling method was voluntary with random replacement; thus, among the women affected by infidelity who visited the aforementioned centers, 30 were selected and then randomly assigned to either the experimental or control group based on a list of names. The instruments used in this study included the Toronto Alexithymia Scale (Taylor, 1986). Data were analyzed using multivariate covariance analysis and mixed analysis of variance with repeated measures design in SPSS 27. Findings: The results indicated that Acceptance and Commitment Therapy was effective in reducing alexithymia in women experiencing infidelity (p < .001, F = 14.065). Conclusion: Consequently, the findings of this study confirm the role and impact of Acceptance and Commitment Therapy in reducing the alexithymia of spouses affected by infidelity.